COOPERATION BETWEEN PARENTS AND PRIMARY SCHOOL TEACHERS IN OVERCOMING THE READING DIFFICULTIES OF PUPILS WITH ATTENTION DEFICIT AND HYPERACTIVITY DISORDER IN PRIMARY CLASSES (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
Nowadays general education schools are increasingly focusing on the development of inclusive education ideas through a variety of social pedagogical assistance measures. Pupils with attention deficit and hyperactivity disorder (ADHD) in primary classes face with learning difficulties (most often with difficulties in reading), often have problems with socialization as well as difficulties in communicating with their peers. Cooperation between parents and primary school teachers in coping with learning difficulties is one of the key factors of effective social pedagogical assistance. The article analyzes the data of qualitative research which reveals the peculiarities of educational difficulties of social pedagogical cooperation, while helping to overcome difficulties (reading) of pupils with ADHD: content, forms and conditions of assistance from parents.
Keywords: primary class pupils with ADHD, reading difficulties, cooperation between teachers and parents, inclusive education.